When, how fast and by how much do trade costs change in the euro area? - Helmut Herwartz; Henning Weber (Kiel University, Department of Economics, 2008)
Microfoundations of the euro's effect on euro area trade hinge on the timing, the speed and the size of adjustment in trade costs. We estimate timing, speed and size of adjustment in trade costs for sectoral trade data. Our approach allows for sector specific impacts of trade costs on sectoral trade while controlling for unobserved but time-variant variables at the sector level. We find that, due to falling trade costs, trade within the euro area increases between the years 2000 and 2003 by 10 to 20 percent compared with trade between European countries that are not members of the euro area. Adjustment of individual sectors is extremely fast whereas aggregate adjustment spreads out because different sectors adjust at distinct times.
Keywords: F42; F13; F33; C33; C31; F15; 330; Euro; Außenwirtschaft; Transaktionskosten; Wirtschaftliche Anpassung; Europäische Wirtschafts- und Währungsunion; EU-Staaten